Pengaruh Standar Operasional Prosedur, Deskripsi Pekerjaan Dan Budaya Kerja Terhadap Kinerja Karyawan PT Sumber Alfaria Trijaya Tbk Cabang Jember - Tamriatin Hidayah; Hary Sulaksono; Hayatul Maspufah (RELASI : JURNAL EKONOMI, 2023)
This study aims to determine the effect of standard operating procedures, job descriptions and work culture on employee performance. In this study, data were collected by means of observation, interviews and questionnaires to 45 respondents with census techniques, which aimed to determine respondents' perceptions of each variable. The analysis used includes data instrument testing (validity test, and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), and hypothesis testing (F test, t test, coefficient of determination). From the results of the analysis using regression, it can be seen that the variables of standard operating procedures (0.575), job descriptions (0.475) and work culture (0.409), all have a positive and significant effect on employee performance. From the t-test, the results obtained are standard operating procedures (0.021), job descriptions (0.014) and work culture (0.001), all of which have a significant effect on employee performance. From the F test, the results of the variable standard operating procedures, job descriptions and work culture have a significant simultaneous effect on employee performance.